OSMOREGULASI PADA HEWAN AKUATIK - Lantu, Sartje (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
All aquatic organisms must deal with the problem of maintaining internal homeostasis, a constant internal chemical environment in which that organism's enzymes can operate efficiently. As we saw earlier, this is largely a matter of osmoregulation, but other factors are involved also. Many marine organisms can get by with minimal osmoregulation since the oceans, where the enzymes evolved, are already a good environment; other marine organisms maintain their body fluids at ionic concentrations different from the surrounding ocean and must actively regulate ions. Freshwater also calls for active measures to maintain proper osmotic balance.